Transformasi Strategi Konten Pada Program Siaran Lentera Iman Di Era Digital: Analisis Interaksi Pengguna Soka Radio Jember Lewat Aplikasi Tiktok Dalam Teori Participatory Culture Henry Jenkins - Anam, Hairul; M. NaufalSani; Syafi’i, Imam (CV. SINAR HOWUHOWU, 2025)
The emergence of radio as a mass medium has facilitated easier access to information for its users. Radio possesses advantages that other mass media do not have. It offers a wide reach, allowing information broadcast through radio to be directed across the globe, especially with its current development supported by the increasing use of the Internet, which further simplifies access to online radio. The religious program “Lentera Iman” is one of the Islamic broadcasting programs presented by Soka Radio FM Sumber Sari Jember, aimed at enhancing listeners’ understanding of Islamic teachings. The transformation of media in the digital era encourages radio to adapt in order to remain relevant amid changing patterns of information consumption. This study aims to analyze how the religious program Lentera Iman on Soka Radio Jember transforms its content strategies through the use of the TikTok application, as well as to explore the forms of user interaction with the content. The findings show that Lentera Iman adapts its content by presenting Islamic messages in short video formats that are more visual, concise, and easily shareable, aligning with the characteristics of TikTok users. User interaction is reflected through comments, likes, and other engagement processes that demonstrate audience involvement in the form of appreciation, religious discussions, and reinterpretations of the conveyed messages. These findings affirm that the use of TikTok enables local radio to expand its reach, enhance interactivity, and create a new space for disseminating religious content that is more inclusive and aligned with the dynamics of digital media.